2010
DOI: 10.1590/s1679-87592010000100004
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal distribution of fish in Palmas bay, Ubatuba, Brazil

Abstract: A B S T R A C TThe aim of this study was to analyze the distribution and abundance of the fish fauna of Palmas bay on Anchieta Island in southeastern Brazil. Specimens were caught in the summer and winter of 1992, using an otter trawl at three locations in the bay. The specimens were caught in both the nighttime and daytime. Data on the water temperature and salinity were recorded for the characterization of the predominant water mass in the region, and sediment samples were taken for granulometric analysis. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
(28 reference statements)
2
14
0
2
Order By: Relevance
“…Araújo et al (2006) described a marked spatial repartition among sciaenid species in the Sepetiba Bay, Rio de Janeiro, and found that Ctenosciaena gracilicirrhus was associated with the outer zone of the bay where depth and transparency are higher, factors associated with more pronounced marine influences. A seasonal repartition of Ctenosciaena gracilicirrhus was also registered by several authors studying areas near the one covered herein, and the species was interpreted as being associated with warmer waters, being present in great numbers near the shore during summer (Rossi-Wongtschowski & Paes, 1993;Rocha & Rossi-Wongtschowski, 1998;Rocha et al, 2010), in accordance with the high abundance of this species at Flamengo Cove in the spring presented herein.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Araújo et al (2006) described a marked spatial repartition among sciaenid species in the Sepetiba Bay, Rio de Janeiro, and found that Ctenosciaena gracilicirrhus was associated with the outer zone of the bay where depth and transparency are higher, factors associated with more pronounced marine influences. A seasonal repartition of Ctenosciaena gracilicirrhus was also registered by several authors studying areas near the one covered herein, and the species was interpreted as being associated with warmer waters, being present in great numbers near the shore during summer (Rossi-Wongtschowski & Paes, 1993;Rocha & Rossi-Wongtschowski, 1998;Rocha et al, 2010), in accordance with the high abundance of this species at Flamengo Cove in the spring presented herein.…”
Section: Discussionsupporting
confidence: 85%
“…Rocha & Rossi-Wongtschowski (1998) also studied the ichthyofauna off the coast of Ubatuba and Caraguatatuba and found similar results, with Ctenosciaena gracilicirrhus and Paralonchurus brasiliensis as the most abundant species. More recently, Rocha et al (2010) investigated the ichthyofauna of Palmas Bay, off the Anchieta Island, a region close to Flamengo Cove. They reported that five species composed more than 73% of their samples, with Ctenosciaena gracilicirrhus as one of the most important in number of individuals in addition to three gerreids and one haemulid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Influence of the SACW on the spatial -temporal distribution of fish, including the sciaenid species, was observed by Rocha et al (2010) in shallow waters in Palmas Bay, Ubatuba. However, the multiple regression analysis indicated the temperature as a significant factor only for the Ubatuba region, probably due to the fact that this region is more exposed than Caraguatatuba which reflects in an intense action of water masses such as SACW.…”
Section: Discussionmentioning
confidence: 98%
“…Cunningham 1983, Nonato et al 1983, Braga & Goitein 1984, Rocha et al 2010). Only two reef fish assessments were carried out in the vicinity of the Anchieta Island State Park (AISP), the protected area focused by the present study.…”
Section: Introductionmentioning
confidence: 99%